2020
DOI: 10.1177/0004563220928361
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 (COVID-19) and the renin-angiotensin system: A closer look at angiotensin-converting enzyme 2 (ACE2)

Abstract: Since the first cases of atypical pneumonia linked to the Huanan Seafood Wholesale Market in Wuhan, China, were described in late December 2019, the global landscape has changed radically. In March 2020, the World Health Organization declared COVID-19 a global pandemic, and at the time of writing this review, just over three million individuals have been infected with more than 200,000 deaths globally. Numerous countries are in 'lockdown', social distancing is the new norm, even the most advanced healthcare sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 62 publications
(177 reference statements)
0
32
0
Order By: Relevance
“…The collection of smoothed daily curves has been analyzed and the deepest curve 59 among every time period a-d has been computed. (10,669) and June 1 st (11,308) gives estimated ratios of 5.316 and 5.254 in these two periods, with an average of around 5.29. This conversion factor was used to backcast the series of real active cases based on the estimated daily official COVID-19 cases in the metropolitan area of A Coruña.…”
Section: Exploratory Flow Studymentioning
confidence: 96%
See 1 more Smart Citation
“…The collection of smoothed daily curves has been analyzed and the deepest curve 59 among every time period a-d has been computed. (10,669) and June 1 st (11,308) gives estimated ratios of 5.316 and 5.254 in these two periods, with an average of around 5.29. This conversion factor was used to backcast the series of real active cases based on the estimated daily official COVID-19 cases in the metropolitan area of A Coruña.…”
Section: Exploratory Flow Studymentioning
confidence: 96%
“…SARS-CoV-2 is an enveloped virus with a nucleocapsid made up of single-stranded RNA bound to protein N (Nucleocapsid), surrounded by a lipid membrane that contains structural proteins M (Membrane), E (Envelop) and S (Spike) [5][6][7][8] . The structure of protein S gives the virus its distinctive crown of spikes and is responsible for binding to the angiotensin-converting enzyme 2 (ACE2) receptor, which allows the virus to enter the host cell 9,10 . ACE2 receptors are present in a range of human cell types, with particular abundance in respiratory and gastrointestinal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of angiotensin-converting enzyme, ACE 2, has also been suggested. Whereas recent discussions have centred on potential sensitivity of ACE 2 inhibitor-treated patients to COVID-19 [ 76 ], clinical trials of ACE 2 antibodies have been suggested [ 77 ].…”
Section: Potential Therapies Of Covid-19mentioning
confidence: 99%
“…SARS-CoV-2 is an enveloped virus with a nucleocapsid made up of single-stranded RNA bound to protein N (Nucleocapsid), surrounded by a lipid membrane that contains structural proteins M (Membrane), E (Envelop) and S (Spike) [5][6][7][8] . The structure of protein S gives the virus its distinctive crown of spikes and is responsible for binding to the angiotensin-converting enzyme 2 (ACE2) receptor, which allows the virus to enter the host cell 9,10 . ACE2 receptors are present in a range of human cell types, with particular abundance in respiratory and gastrointestinal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%